Low maternal pertussis protection and quantified infant risk: supporting maternal Tdap vaccination in China - Wang, Wen; Zhang, Tingting; Sun, Xiang (Frontiers in Immunology, 2026)
BackgroundPertussis remains a significant threat to infants, particularly in settings like China, where maternal tetanus-diphtheria-acellular pertussis (Tdap) vaccination is not part of the National Immunization Program, and data on maternal pertussis immunity are limited. This study aimed to assess the seroprevalence of protective pertussis toxin (PT) IgG antibodies in pregnant women and quantify the potential risk of infant pertussis under varying epidemiological scenarios.MethodsA cross-sectional serosurvey was conducted among 1,205 pregnant women in Jiangsu Province, China, from January to December 2024. Serum anti-PT IgG concentrations were measured using ELISA, with a protective threshold defined as ≥40 IU/mL. A scenario-based risk model (Pinfant =(1− pm)×Iw×E×T) was developed to estimate infant pertussis risk (0–6 months) by linking maternal protection proportion (pm), age-specific incidence in childbearing-age women Iw), exposure window (E), and mother-to-infant transmission probability (T).ResultsThe overall median anti-PT IgG concentration was 6.34 IU/mL (IQR: 4.24–11.16), with only 3.57% (95% CI: 2.66–4.77%) of women achieving the protective threshold (≥40 IU/mL). Under a representative scenario (Iw = 50/100,000, T = 0.20), the model estimated 4.82 infant cases per 100,000 births under current immunity, reduced to 1.00 cases with maternal Tdap (pm = 80.0%), a 79.2% relative reduction. Higher incidence and transmission scenarios yielded greater absolute reductions with vaccination.ConclusionLow maternal pertussis immunity in China poses a quantifiable risk to infants, particularly under elevated incidence scenarios. Maternal Tdap vaccination could substantially reduce infant pertussis burden, supporting its consideration for national immunization policy. These findings provide critical evidence for addressing immunity gaps and protecting vulnerable newborns in China.